Commander's leadership style, behavior and knowledge in motivating non-commissioned officers in the Malaysian Infantry - Nixon, A. Endry (2012)
The aim of motivatmg soldiers is to sustain the soldiers' desire, commitment and willingness to perform their military missions effectively in the interest of the nation. As motivation is an essential fuctor in the military and studies in motivation are limited in the Malaysian Infantry, the need to identify motivating factors important to non-commissioned officers and determine the factors that enable military commanders to motivate their non-commissioned officers becomes a necessity for study. The primary objectives of this study is to identify the motivation factors that are important to non-commissioned officers and detennine military commander's leadership style, behavior and level of knowledge in motivating non-commissioned officers in the Malaysian Infantry. A quantitative approach was taken where questionnaire survey were distributed to non-commissioned officers, subordinate military officers and military commanders in the Malaysian Infantry and data obtained were analyzed using descriptive, correlation coefficients, collinearity test and multiple linear regression analyses. The findings revealed that among the motivation factors examined, sense of loyalty, espirit de corp and role clarity were ranked as the most important motivation factors while interesting work was ranked the lowest among the non-commissioned officers and that it changes according to their career in their military service. In examining the factors to enable military commanders to motivate their non-commissioned officers, the multiple linear regression model revealed that transactional leadership, transformational leadership, task-oriented behavior, people-oriented behavior, and level ofknowledge were found to contribute significantly to theory and practice in motivating non-commissioned officers. The contributions of this study are fivefold. For the body of knowledge, first; two models were developed in ranking motivation factors that are of high and low importance and changes in motivational needs during military career of non-commissioned officers in the Malaysian Infantry, second; it supports motivation theories by indicating changes in motivational needs as one progresses in career, third; it provides a comparison and indicates a significance of leadership style; transactional and transformational; behavior; task and people oriented behavior and knowledge among military commanders in motivating non-commissioned officers in the Malaysian Infantry. Fourth, for practice, it indicates the awareness of motivation factors and the level ofneeds amon&..the non-commissioned officers for military commanders and the Malaysian Infantry to address. Fifth, for policy, it provides new insights of emphasis in military commanders' future training policy, specifically in leadership style and behavior for the Malaysian Infantry. The study has contributed to the body of knowledge,practice and policy, specifically to the Malaysian Infantry to continually enhance human resource management among their military commanders.